Bodily memories and writing that arises from the body: processes in performing arts in the Pedagogy course (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article addresses a teacher education process based on performing arts in the Pedagogy course that aroused bodily memories that were decisive for the research topic regarding the perceptions of Early Childhood Education professionals regarding the constitution of the bodies of girls and boys. The research has a qualitative approach, bibliographical character, field insertion and involved the autobiographical narrative. The results indicate that reflecting on marks registered in the body facilitates the establishment of connections relevant to pedagogical practice, promotes powerful education aimed at reducing gender discrimination and mobilizes teachers to prioritize children's points of view.
Keywords: body; performing arts; teacher educación; writing